2012
DOI: 10.5402/2012/604389
|View full text |Cite
|
Sign up to set email alerts
|

Sol-Gel Thin Films Immobilized with Bromocresol Purple pH-Sensitive Indicator in Presence of Surfactants

Abstract: Preparation of transparent sol-gel thin film immobilized with bromocresol purple (BCP) pH-sensitive indicator was made via the acid catalyzed sol-gel reaction of tetraethylorthosilicate and the bromocresol purple indicator (BCP). Different surfactants include cationic cetyl trimethyl ammonium bromide (CTAB), anionic sodium dodecyl sulfate (SDS), and nonionic Triton X-100 (TX-100) were used to improve the mesostructure of the host material and to increase its porosity. The color change behavior of the immobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 20 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…The pKa of BCP in the ionogel was determined using standard buffer solutions ( comparison to a pK a of 6.3 reported in literature 55 . It was previously demonstrated that when pH indicator dyes are immobilised within solid gels, the micro-environment of the matrix shifts the pK a of the dye slightly, on occasions by over 0.5 pH unit 56 .…”
Section: Calibration Of the Chemical Sensormentioning
confidence: 99%
“…The pKa of BCP in the ionogel was determined using standard buffer solutions ( comparison to a pK a of 6.3 reported in literature 55 . It was previously demonstrated that when pH indicator dyes are immobilised within solid gels, the micro-environment of the matrix shifts the pK a of the dye slightly, on occasions by over 0.5 pH unit 56 .…”
Section: Calibration Of the Chemical Sensormentioning
confidence: 99%
“…The same group also reported on TEOSbased films doped with chlorophenol red which was used to monitor the acidity around stained glass windows in Madrid [95]. The influence of the surfactants on sol-gel-based pH sensor response was also investigated [96,97]. The TEOSbased sol was doped with bromocresol red and three different surfactants, namely cationic cetyl trimethyl ammonium bromide, anionic sodium dodecyl sulfate (SDS) and non-ionic Triton X-100.…”
Section: Absorption-based Ph Co 2 and Nh 3 Sensorsmentioning
confidence: 98%
“…Even though significant advances in technologies based on sol-gel thin film processing have been reported [1][2][3][4][5][6][7], still relatively little efforts are directed toward understanding the different pH-sensing dyes' immobilization behavior into sol-gelbased silica matrices without leaching problem [8][9][10]. These can be used for designing photocatalysts, for water detection, and also for developing the novel chemical sensor materials [11].…”
Section: Introductionmentioning
confidence: 98%
“…To solve this issue, in this study, we propose two types of matrices, titania and silica-titania by sol-gel method at low temperature. There are three methods to immobilize indicator into sol-gel matrix: covalent binding, impregnation, and chemical doping [1]. The chemical doping sol-gel method allows fast application of the coating solution without damaging film and is quite attractive to prepare nanomaterials by hydrolysis and polycondensation of different precursors in liquid and to immobilize the dyes (guests) into fabricated nanomaterials host network for photocatalysis and sensing applications.…”
Section: Introductionmentioning
confidence: 99%